Diagnosing and managing psychosis in primary care. - Saunders, K; Brain, S; Ebmeier, K (2011)
Psychosis is broadly defined as the presence of delusions and hallucinations. It can be organic or functional. The former is secondary to an underlying medical condition, such as delirium or dementia, the latter to a psychiatric disorder, such as schizophrenia or bipolar disorder. The identification and treatment of psychosis is vital as it is associated with a 10% lifetime risk of suicide and significant social exclusion. Psychosis can be recognised by taking a thorough history, examining the patient's mental state and obtaining a collateral history. The history usually enables a distinction to be made between bipolar disorder, schizophrenia and other causes. Early symptoms often include low mood, declining educational or occupational functioning, poor motivation, changes in sleep, perceptual changes, suspiciousness and mistrust. The patient's appearance, e.g. unkempt or inappropriately attired, may reflect their predominant mental state. There may be signs of agitation, hostility or distractibility. Speech may be disorganised and difficult to follow or there may be evidence of decreased speech. Mood may be depressed or elated or change rapidly. Patients may describe abnormal thoughts and enquiry into thoughts of suicide should be routine. Disturbances of thought such as insertion or withdrawal may be present along with perceptual abnormalities i.e. illusions, hallucinations. Insight varies during the course of a psychotic illness but should be explored as it has implications for management. All patients presenting with first episode psychosis for which no organic cause can be found should be referred to the local early intervention service. In patients with a known diagnosis consider referral if there is: poor response or nonadherence to treatment; intolerable side effects; comorbid substance misuse; risk to self or others.